Fasting insulin levels independently associated with coronary heart disease in non-diabetic Turkish men and women - Onat, A; Ceyhan, K; Sansoy, V; Basar, Ö; Erer, B; Uysal, Ö; Hergenç, G (ELSEVIER SCI IRELAND LTD, 2002)
Background: Levels of plasma insulin have been recognized as a weak risk indicator for coronary or cardiovascular risk in the general population with ethnic background and gender modifying this relationship. We assessed whether insulin concentrations are associated with or would serve as a marker of prevalent coronary heart disease risk in a cross-sectional study of a population having low cholesterol levels Oust under 5 mmol/l) but higher prevalence of components of the metabolic syndrome. Methods: In 688 participants of the Turkish Adult Risk Factor Survey in 2001, plasma insulin values as well as other risk variables were evaluated, and coronary heart disease was diagnosed based on clinical findings and Minnesota coding of resting electrocardiograms. Nearly equal numbers of men and women (>30 years of age) constituted the population sample from the two largest regions of Turkey. Concentrations of insulin were determined by the chemiluminescent immunometric method. Results: Geometric mean value was 50 pmol/l (interquartile range 37-68 pmol/l), without revealing a significant difference in genders. Fasting insulin was correlated in both genders with many variables, notably those involving central obesity, triglycerides, blood pressure, physical inactivity and, inversely, with high-density lipoprotein (HDL)-cholesterol. In a regression model, waist circumference and body mass index were strongly associated with log insulin, after controlling for age and presence of coronary heart disease. The age- and obesity-adjusted odds ratio for coronary heart disease in the highest as opposed to the lowest quartile was 2-fold in both genders (P<0.05). Even after adjustment for dyslipidemia, blood pressure, glucose intolerance, physical activity and smoking status, an over 2-fold increased coronary heart disease risk still persisted with regard to hyperinsulinemia (greater than or equal to10 mU/l, 69.5 pmol/l). When C-reactive protein which was correlated with fasting insulin only in women, was added to the model, the impact of hyperinsulinemia on coronary heart disease risk remained unchanged. Conclusion: Hyperinsulinemia (i) may provide information on the coronary heart disease likelihood over and above that provided by the other risk factors, including HDL-cholesterol, and (ii) may contribute, within the frame of insulin resistance, to the coronary heart disease risk independently of the classical risk factors. (C) 2002 Elsevier Science Ireland Ltd. All rights reserved.
Keywords: hyperinsulinemia; coronary heart disease; inflammation; risk assessment; CARDIOVASCULAR-DISEASE; RISK-FACTORS; RESISTANCE SYNDROME; CHOLESTEROL LEVELS; NONDIABETIC MEN; PLASMA-INSULIN; ELDERLY MEN; FOLLOW-UP; ATHEROSCLEROSIS; Cardiovascular System & Cardiology